STONE FRUITS AS VALUABLE SOURCES OF PECTIN - Ruziboy, Normakhmatov (International Journal of Membrane Science and Technology, 2023)
The article contains the results of the studies on the content of pectic substances in three pomological varieties of apricot fruits, in three pomological varieties of peach and three pomological varieties of plum fruits grown in the climatic conditions of the Republic of Uzbekistan. The studies have shown that stone fruits as apricots, peaches and plums grown in Uzbekistan are characterized by a high content of pectin. According to our research, the variety Yubileyniy (anniversary) Navoi turned out to be the richest in pectic content from the studied fruit varieties, where the average content is 1.32%; in the Raspberry variety of peaches it is 1.12%; in the Violet Hungarian variety of plums, the average content is 1.32%. In all other studied varieties of apricot, peach and plum fruits, the content of pectic substances is more than one percent, with the exception of the fruits of the Yaichnaya (eggy) yellow plum variety where the average content of pectic substances is 0.93%. Due to the high content of pectic substances with good gelling properties, the studied pomological varieties of stone fruits can be successfully used to obtain a number of confectionery products with a jelly-like consistency.